IMPLEMENTATION OF THE INDEPENDENT CURRICULUM IN PAI-BP LEARNING AT SMA N 3 PANYABUNGAN - Khoirul Amri Rambe; Muhammad Ikbal; Melda Diana Nasution (Journal International Inspire Education Technology, 2025)
SMA Negeri 3 Panyabungan is one of the schools that has implemented the Independent Curriculum starting from the 2022/2023 school year and is one of the driving schools in Mandailing Natal Regency. This study discusses: 1) How to apply the Independent Curriculum in PAI-BP learning at SMA Negeri 3 Panyabungan, 2) Supporting and inhibiting factors for the implementation of the Independent Curriculum in PAI-BP learning at SMA Negeri 3 Panyabungan. The purpose of this study is to find out the application and the supporting and inhibiting factors. This type of research is classified as qualitative research with primary and secondary data sources. The data collection method uses observation, interviews, and documentation. The results of the study show that the implementation of the Independent Curriculum at SMA Negeri 3 Panyabungan has reached the highest option, namely independent sharing. In this option, schools have the flexibility to implement the Independent Curriculum by developing their own teaching tools, which show the school's full readiness. This readiness is also reflected in the existing human resources, where many students produce innovative works. Supporting factors include its status as a driving school, the number of driving teachers, and the balance between projects and character cultivation. However, there are challenges such as lack of student motivation, limited time and teacher readiness, limited learning media, and the need to improve evaluation.